Progesterone influences cytoplasmic maturation in porcine oocytes developing in vitro - Yuan,Bao; Liang,Shuang; Jin,Yong-Xun; Kwon,Jeong-Woo; Zhang,Jia-Bao; Kim,Nam-Hyung (PeerJ, 2016)
Progesterone (P4), an ovarian steroid hormone, is an important regulator of female reproduction. In this study, we explored the influence of progesterone on porcine oocyte nuclear maturation and cytoplasmic maturation and development in vitro. We found that the presence of P4 during oocyte maturation did not inhibit polar body extrusions but significantly increased glutathione and decreased reactive oxygen species (ROS) levels relative to that in control groups. The incidence of parthenogenetically activated oocytes that could develop to the blastocyst stage was higher (p < 0.05) when oocytes were exposed to P4 as compared to that in the controls. Cell numbers were increased in the P4-treated groups. Further, the P4-specific inhibitor mifepristone (RU486) prevented porcine oocyte maturation, as represented by the reduced incidence (p < 0.05) of oocyte first polar body extrusions. RU486 affected maturation promoting factor (MPF) activity and maternal mRNA polyadenylation status. In general, these data show that P4 influences the cytoplasmic maturation of porcine oocytes, at least partially, by decreasing their polyadenylation, thereby altering maternal gene expression.
Keywords: Progesterone; Mifepristone; Pig oocyte; In vitro maturation (IVM); Embryonic development